Pharmacotherapy of heart failure with normal ejection fraction (HFNEF) – a systematic review - Rajagopalan, Sujit (Blackwell Science Inc, 2011)
AIM: The pharmacotherapy for heart failure with normal ejection fraction (HFNEF) is not as well defined as that for the treatment for heart failure with reduced ejection fraction (HFREF). Studies of the various drugs given for HFNEF have revealed conflicting results. The aim of this systematic review was to determine whether there is any benefit with pharmacotherapy in HFNEF in terms of cardiac outcomes. METHODS: Electronic and printed sources were searched until August 2010 for randomized controlled clinical trials (RCTs) comparing drug therapy with placebo in HFNEF. Weighted mean difference and pooled odds ratio (OR) with 95% confidence intervals were calculated. RESULTS: A total of six RCTs including 8410 patients with a mean follow-up period of 21 months were included in the analysis. Although there were no significant differences in all cause mortality between the two groups (pooled OR 0.95, 95% CI 0.79, 1.13, P = 0.55), the subgroup analysis revealed a slight but non significant advantage with the β-adrenoceptor blocker group. There was no significant difference between the two groups in terms of cardiovascular mortality, hospitalization, worsening heart failure, ejection fraction, E : A ratio, deceleration time and E : E′ ratio. CONCLUSION: There was no significant benefit of pharmacotherapy in HFNEF. This might have been because of a lack of stringent inclusion criteria for patients in the trials and lower power of the studies. Hence trials with well defined inclusion criteria, better power, longer follow-up periods and with echocardiographic parameters as endpoints are required to shed further light on this topic.